Basic Models Modeling Resistance Training: An Update for Basic Scientists Interested in Study Skeletal Muscle Hypertrophy. Issue 9 (September 2014) - Cholewa, Jason; Guimarães‐Ferreira, Lucas; da Silva Teixeira, Tamiris; Naimo, Marshall Alan; Zhi, Xia; de Sá, Rafaele Bis Dal Ponte; Lodetti, Alice; Cardozo, Mayara Quadros; Zanchi, Nelo Eidy
Abstract Human muscle hypertrophy brought about by voluntary exercise in laboratorial conditions is the most common way to study resistance exercise training, especially because of its reliability, stimulus control and easy application to resistance training exercise sessions at fitness centers. However, because of the complexity of blood factors and organs involved, invasive data is difficult to obtain in human exercise training studies due to the integration of several organs, including adipose tissue, liver, brain and skeletal muscle. In contrast, studying skeletal muscle remodeling in animal models are easier to perform as the organs can be easily obtained after euthanasia; however, not all models of resistance training in animals displays a robust capacity to hypertrophy the desired muscle. Moreover, some models of resistance training rely on voluntary effort, which complicates the results observed when animal models are employed since voluntary capacity is something theoretically impossible to measure in rodents. With this information in mind, we will review the modalities used to simulate resistance training in animals in order to present to investigators the benefits and risks of different animal models capable to provoke skeletal muscle hypertrophy. Our second objective is to help investigators analyze and select the experimental resistance training model that best promotes the research question and desired endpoints. J. Cell. Physiol. 229: 1148–1156, 2014. © 2013 Wiley Periodicals, Inc.